DEM simulation of mortar-bolt interface behaviour subjected to shearing - Shang, Junlong (2020)
In this study, a 3D DEM model containing a mortar-bolt interface subjected to shearing was established in the context of the simplified rock bolt model (SRBM) proposed in a companion paper. The DEM model was calibrated against a series of laboratory experiments to reproduce the mechanical characteristics of a cement mortar with a uniaxial compressive strength of 30 MPa. The DEM simulation has led to a detailed observation and an in-depth understanding of the mode II progressive debonding of the mortar-bolt interface and subsequent mortar rupture (due to mechanical interlocking). In addition, the effects of particle size of mortar and profile configurations of rebar bolts (i.e., different rib spacings and rib heights) on simulation results were discussed. The numerical findings in the study were validated against laboratory measurements and a broad agreement was observed.